2019
DOI: 10.1016/j.jamcollsurg.2019.08.1259
|View full text |Cite
|
Sign up to set email alerts
|

Summative Supervisor Reporting: A Quality Performance Perspective

Abstract: Objective: This study aimed to quality assure Assigned Educational Supervisor (AES) reports, using UK Joint Committee on Surgical Training (JCST) objective criteria, to evaluate contribution Annual Review of Competence Progression (ARCP). Design: Consecutive 145 AES reports from 75 trainers regarding 68 Core Surgical Trainees were assessed from 9 hospitals (2 Tertiary centres (77 reports), 7 District General Hospitals (68 reports)). Reports were assessed by independent assessors based on free text related to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…24 Unfortunately, a study of the quality of ES reports to the ARCP demonstrated that less than 30% were 'satisfactory'. 25 The main issues are related to failure to review all the evidence (specifically the logbooks and comments from clinical supervisors) and failure to use the free text tools to expand on or justify the recommendation given.…”
Section: Educational Supervisor's Reportmentioning
confidence: 99%
“…24 Unfortunately, a study of the quality of ES reports to the ARCP demonstrated that less than 30% were 'satisfactory'. 25 The main issues are related to failure to review all the evidence (specifically the logbooks and comments from clinical supervisors) and failure to use the free text tools to expand on or justify the recommendation given.…”
Section: Educational Supervisor's Reportmentioning
confidence: 99%